ANALISIS PENGUKURAN KINERJA PADA KOPERASI DENGAN METODE BALANCED SCORECARD (Studi Pada Koperasi Karyawan Pembangunan PT. PLN (Persero) Samarinda - Darmawan, - Donny (EKONOMIA, 2019)
The purpose of this study was to determine and analyze the performance of the Employee Development Cooperative PT. PLN in 2015 and 2016 based on the Balanced Scorecard method. The analytical tool used in this study is ROA (Return On Assets), ROE (Return On Equity), Customer Acquisition, Customer Retention, Service Error Rate, Respond Time, Product Innovation and Employee Productivity. Based on the results of the conclusions obtained from the research that the financial perspective seen from ROA is considered less this shows the ability of the cooperative to produce a decrease in total assets and ROE is considered less this is shown in the ability of the cooperative to obtain profits from its total equity has decreased. The customer's perspective on Customer Acquisition and Customer Retention is sufficient and lacking in performance, this is indicated by the rate of acquisition and retention that has decreased. Internal business process perspective can be seen from the employee's performance can be considered good this is indicated by the level of employee error in providing services experiencing a decrease and Respond Time percentage has increased. Learning and growth perspectives seen from employee productivity employee performance is considered sufficient this is shown in cooperative operating income from the number of employees available.